PELATIHAN PEMBUATAN KERUPUK IKAN DALAM UPAYA MENINGKATKAN PEREKONOMIAN MASYARAKAT - Setiyadi, Muhammad Wahyu; Kamaluddin, Kamaluddin; Andika , I Putu Herry Widhi; Kusuma, Ketut Chandra Adinata; Pratama, Susilo Suherman; Fatimah, Fatimah; Sutajaya, I Made; I Gusti Putu (Universitas Mataram, 2024)
Almost all coastal locations in Indonesia have stagnated the selling value of marine products. This is due to the habits of Indonesian people in processing marine products. One place in Soro Village in Kempo District, Dompu Regency, West Nusa Tenggara has this kind of problem. Soro, which is part of Kempo sub-district, is the largest fishing community base in Saleh Bay. In connection with that, the pancaharian eyes of the people of Soro village are mostly fishermen and also those with pancaharia eyes of farmers. This activity provides training to the local community, especially those who work as fishermen. The training included making crackers from fish-based ingredients produced by local fishermen. The type of fish used is Cob fish. The method in implementing this activity is a socialization and demonstration method consisting of the stages of preparation, implementation, supervision and evaluation. The level of knowledge of trainees is measured through interviews conducted before and after training activities, and findings. The results of this service resulted in fish crackers, as well as increased public knowledge in processing fish raw materials into fish crackers increased to improve the economy of citizens. This PKM activity was able to make an extraordinary contribution to the participants, namely providing the ability for residents to process fish into healthy crackers. Community entrepreneurship insights increased and encouraged participants to take advantage of the business opportunities of processing fish crackers to increase income and help family finances.